Inorganic reaction mechanisms. A personal journey - Hubbard, Colin; Chatterjee, Debabrata; Oszajca, Maria; Polaczek, Justyna; Impert, Olga; Chrzanowska, Marta; Katafias, Anna; Puchta, Ralph; van Eldik, Rudi (Dalton Transactions, 2020)
This review covers highlights of the work performed in the van Eldik group on inorganic reaction mechanisms over the past two decades in the form of a personal journey. Topics that are covered include, from NO to HNO chemistry, peroxide activation in model porphyrin and enzymatic systems, the wonder-world of RuIII(edta) chemistry, redox chemistry of Ru(iii) complexes, Ru(ii) polypyridyl complexes and their application, relevant physicochemical properties and reaction mechanisms in ionic liquids, and mechanistic insight from computational chemistry. In each of these sections, typical examples of mechanistic studies are presented in reference to related work reported in the literature.
CRIS-Team Scopus Importer:2020-04-28